Genotypic and antimicrobial susceptibility of Streptococcus agalactiae causing bovine mastitis in the central region of Thailand - Wataradee, Sirirat; Samngamnim, Sukuma; Boonserm, Thanasak; Ajariyakhajorn, Kittisak (Frontiers in Veterinary Science, 2023)
Introduction Streptococcus agalactiae is a highly contagious pathogen that causes bovine mastitis, leading to significant economic losses. This study aimed to (1) identify and characterize S. agalactiae strains responsible for bovine mastitis by examining their phenotypic and genotypic characteristics in Thai dairy-intensive farming areas and (2) determine their susceptibility profiles to antimicrobial agents. Material and methods In total, 100 S. agalactiae isolates obtained from clinical and subclinical mastitis cases from 13 dairy herds located in the central region of Thailand were examined. To confirm the identity of the bacterial pathogens, conventional microbiological procedures recommended by the National Mastitis Council (NMC) and the VITEK® 2 system were employed. Results All 100 isolates were successfully identified as S. agalactiae using the NMC procedure, whereas 94 isolates were identified as S. agalactiae using the VITEK® 2 system. Finally, the S. agalactiae-specific gene dlt S was identified in all the examined isolates using polymerase chain reaction. Capsular polysaccharide (CPS) typing revealed that all strains belonged to CPS type Ia. Multilocus sequence typing identified 33 selected isolates as sequence type 103. Random amplified polymorphic DNA (RAPD) typing yielded 43 RAPD types, with 6 RAPD clusters identified. These results demonstrated a high level of genetic diversity among S. agalactiae within the studied herds. RAPD analysis suggested that specific S. agalactiae strains could persist in dairy farms for 2–12 months. Furthermore, antimicrobial susceptibility testing was performed using the broth microdilution method. Most strains demonstrated susceptibility to ampicillin, penicillin, penicillin/novobiocin, cephalothin, oxacillin, ceftiofur, and erythromycin. Discussion This study revealed the phenotypic and genotypic characteristics of S. agalactiae isolates responsible for bovine mastitis in the central region of Thailand. The rapid identification of S. agalactiae and application of molecular typing methods can provide valuable epidemiological information regarding S. agalactiae causing mastitis in dairy farms. The antimicrobial susceptibility of S. agalactiae indicates that antimicrobial treatment for control and eradication could be a successful protocol. Our findings revealed that a single clonal strain of S. agalactiae affected the 13 studied farms. Further research is needed to explore the feasibility of vaccine development and application.